Developing a database for multicenter evaluation of placenta accreta spectrum. (2nd April 2021) - Braun, Thorsten; van Beekhuizen, Heleen J.; Morlando, Maddalena; Morel, Olivier; Stefanovic, Vedran; ,
Abstract: Studies of rare, but complex clinical conditions require multicenter cooperation. The International Society for Placenta accreta spectrum (IS‐PAS) have established a secure web‐based database to analyze pregnancies complicated by PAS. By repeated in‐person meetings of the IS‐PAS, a core dataset was established. Then, a custom‐made, secure online database, capable of receiving strictly anonymized patient‐related textual and imaging data and allowing statistical queries was designed, tested, amended and implemented. Between 2008 and 2019, 14 IS‐PAS centers across Europe and one center in the USA contributed data for all their PAS cases, containing pregnancy data for a total of 442 pregnant women. Data were analyzed by a designated data analysis sub‐group of the IS‐PAS. Center characteristics are presented. Based on experiences with previous versions, our new online database now allows an all‐encompassing data collection. It has shown its usefulness in the current analysis project.